Biologia reprodutiva de fêmeas de laetacara araguaiae (labriformes: cichlidae) - Silva, Amanda Pereira dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Laetacara araguaiae is a species of south American ciclideo described in the Araguaia river basin, São Miguel do Araguaia, Goias, Brazil by Ottoni and Costa (2009). The description of reproductive phases is being performed some time ago with the analysis of the annual reproductive cycle, that is based on stages of gonadal maturation of analyzed species. The objective of this work was to describe morphologically the reproductive cycle of female L. araguaiae. Were collected from 80 females of L. araguaiae, in the period April/2012 to March/2013, in Two Streams, river Selviria, Mato Grosso do Sul, Brazil. The ovaries were processed, using techniques for light microscopy and transmission electron microscopy. Even were identified phases of the reproductive cycle that apply to females, gonadossomatico index (GSI) and size of first ovarian maturation. The oogenesis presented germinative epithelium with three types of oogonias and oocytes in phase of profase of meiosis for the formation of the ovarian follicles. Primary Growth with the presence of oocytes pre-vitelogenicos and oocytes cortical alveoli and secondary growth or vitelogenese, characterized by initial deposition of granules of yolk. The event which characterizes the maturation stage is the migration from the nucleus to the periphery of the oocyte toward through. The follicular suffered complex morphological changes along the stages of oocytes. In addition, for Laetacara araguaiae were defined five reproductive phases throughout the year: immature, development, able to spawning, regression and regeneration. The average length of first ovarian maturation was estimated at 2.0 cm standard length. The mature individuals (able to spawn) were captured from September to coincide with the seasons of spring and summer. The IGS showed high average values in phase of able to spawn (4,528) and the lowest average values in immature (0.502). The seasons of the year in which the individual is able ...

Laetacara araguaiae é uma espécie de ciclídeo sul-americano descrito na bacia do rio Araguaia, São Miguel do Araguaia, Goiás, Brasil por Ottoni e Costa (2009). A descrição das fases reprodutivas vem sendo realizada há algum tempo com a análise do ciclo reprodutivo anual, que se baseia nas fases de maturação gonadal de espécies analisadas. O objetivo do trabalho foi descrever morfologicamente o ciclo reprodutivo de fêmeas de L. araguaiae. Foram coletadas 80 fêmeas de L. araguaiae, no período abril/2012 a março/2013, no rio Dois Córregos, Selvíria, Mato Grosso do Sul, Brasil. Os ovários foram processados, utilizando-se técnicas para microscopia de luz e microscopia eletrônica de transmissão. Ainda foram identificadas as fases do ciclo reprodutivo que se aplicam as fêmeas, índice gonadossomático (IGS) e tamanho da primeira maturação ovariana. A oogênese apresentou epitélio germinativo com três tipos de oogônias e oócitos em fase de prófase da meiose para a formação dos folículos ovarianos. Crescimento primário com a presença de oócitos pré-vitelogênicos e oócitos alvéolos corticais e crescimento secundário ou vitelogênese, caracterizado pela deposição inicial de grânulos de vitelo. O evento, que caracteriza o estágio de maturação é a migração do núcleo para a periferia do oócito em direção à micrópila. O complexo folicular sofreu modificações morfológicas ao longo dos estágios dos oócitos. Alem disso, para Laetacara araguaiae foram definidas cinco fases reprodutivas ao longo do ano: imaturo, desenvolvimento, apto a desova, regressão e regeneração. O comprimento médio da primeira maturação ovariana foi estimado em 2,0 cm de comprimento padrão. Os indivíduos maduros (aptos à desova) foram capturados a partir de setembro que coincidem com as estações de primavera e verão. O IGS apresentou valores médios elevados na fase de apto a desova (4,528) e os menores valores médios ...
Keywords: Peixe - Reprodução; Peixe - Morfologia; Oogenese; Fishes Reproduction